In vitro analysis of matrix proteins and growth factors in dedifferentiating human chondrocytes for tissue-engineered cartilage - Gößler, Ulrich; Bugert, Peter; Bieback, Karen; Sadick, Haneen; Verse, Thomas; Baisch, Alexander; Hörmann, Karl; Riedel, Frank (Acta oto-laryngologica, 2005)
ConclusionsWith ongoing culture and dedifferentiation of chondrocytes, significant changes in the expression patterns of various collagens and the insulin-like growth factor (IGF) receptor were detected. The latter could play an important role in the differentiation of human chondrocytes.ObjectiveTissue engineering represents a promising method for the construction of autologous chondrogenic grafts for reconstructive surgery. So far, little is known about the expression of markers for cell proliferation and differentiation in cultured chondrocytes.Material and methodsHuman chondrocytes were isolated from septal cartilage (n=5) and held in primary cell culture. Cells were harvested after 24 h and 6 days. Proliferation was analyzed using an Alamar Blue assay. The differentiation of the cells was investigated using bright field microscopy, the expression patterns of various proteins using immunohistochemistry and the expression of distinct genes using a microarray technique.ResultsThe chondrocytes showed strong proliferation (Day 0: 16.7±0.7 fluorescent units; Day 5: 52.4±2.2 fluorescent units) from the third day of cell culture in medium without growth factors. From this point onwards, a dedifferentiation of the chondrocytes could be observed. In cell culture, the chondrocytes expressed collagen 1 and 10 without expression of collagen 3. After 6 days of cell culture, they expressed collagen 2. The chondrocytes showed constant low expression of the fibroblast growth factor-2 receptor, but constant high expression of vascular endothelial growth factor, matrix metalloproteinase (MMP)2 and MMP9. The cells never expressed the epidermal growth factor receptor. The proportion of IGF receptor-expressing cells diminished significantly during cell culture.
Elektronische Reproduktion der Druckausgabe
Gesehen am 01.04.2022